Fire ROS Calculator: A Tool to Measure the Rate of Spread of a Propagating Wildfire in a Laboratory Setting - Abouali, Abdelrahman (2019)
The Fire ROS Calculator is a software tool built using MATLAB to assist researchers from the wildfire research area in analysing wildland fire behaviours. In particular, it measures the rate of spread (ROS) of a fire propagating over a surface in a laboratory setting and constructs its propagation contour map. An algorithm is used to calibrate the camera used for filming the fire spread. Various algorithms and image processing procedures are applied to the images to obtain the ROS. The software has a graphical user interface (GUI) and documentation stored in a GitHub repository alongside the source code.